海氷の層状微視組織形成のボロノイダイナミクスシミュレーション - 河野, 義樹; 大橋, 鉄也 (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series A, 2008)
Developments of sea ice polycrystals from the sea surface are simulated in two-dimensional approximation by combining numerical methods for crystal growth, salinity diffusion and flux of heat. An anisotropic growth of ice crystals from a number of nuclei and their mutual impingements are numerically reproduced by a simple and novel technique, named Voronoi dynamics. Discharge of salt from solidified region and salinity condensation at the solid-liquid interface are also taken into consideration. Diffusion process of salinity and heat flux are evaluated by solving equations for diffusion and heat conduction, and growth of ice crystals is affected by these two factors. Results show that a layer of granular grains is formed near the sea surface and columnar shaped grains develop below it. Brine regions are mainly formed along grain boundaries in the layer of granular grains. In the region of columnar shaped grains, brine regions exist not only along grain boundaries but also inside grains. Columnar shaped crystal grains consist of ice platelets growing in the vertical direction and brine layers between them. These microstructural features are in accordance with experimental observations. journal article